Reduction of cement consumption by the aid of silica nano-particles (investigation on concrete properties) - Bahadori, Hadi; Hosseini, Payam (Journal of Civil Engineering and Management, 2012)
In this study, effects of replacing cement with colloidal amorphous silica nano-particles have been experimentally investigated on the physical and mechanical properties, durability and microstructure of concrete. Experimental results include workability, fresh concrete density, and hardened concrete properties like compressive strength at different ages of 3, 7, and 28-days, and also 28-days splitting tensile strength. Furthermore, influence of silica nano-particles on durability and microstructure of concrete for 28-days specimens was tested by conducting water absorption test, Scanning Electron Microscopy (SEM), and Energy Dispersive X-ray Analysis (EDAX), respectively. In order to study the effect of replacement of cement with silica nano-particles, specimens with 10%, 20%, and 30% cement reduction, and addition of 1%, 2%, and 3% silica nano-particles with respect to witness specimen were fabricated. Experimental results revealed that 20% reduction of cement combining 2% silica nano-particles and also 10% cement reduction combined with 1% silica nano-particles enhance the microstructure of concrete, despite unnoticeable compressive and tensile strength loss. By remarkable reduction of cement consumption and addition of silica nano-particles, strength almost remains constant and consequently decreasing the cement content will become possible. Also, in all specimens, increase in nano-particles content and decrease in cement usage contributed to workability loss. Therefore, applying super-plasticizers seems indispensible while using silica nano-particles. On the other side, according to water absorption test, concretes containing nanoparticles showed more appropriate durability.